COUNTRY FOCUS Development of Micro, Small and Medium Enterprises in Bangladesh - Tulus T.H. Tambunan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
It is hard to find official annual data and government’s comprehensive reports on micro, small and medium enterprises (MSMEs) in Bangladesh. Moreover, the country does not have a uniform national definition of MSME, and the definition has changed overtime in different industrial policies announced by the government in different years. Therefore, in this country focus, instead on one official source of information, it is based on various sources, including selected journal articles, papers and survey data from various agencies such as the Bangladesh Bureau of Statistics (BBS), the International Consultancy Group (ICG) of the United Kingdom (UK) and the Micro Industries Development Assistance and Services (MIDAS), and the International Monetary Fund (IMF).